2016
DOI: 10.1111/imm.12573
|View full text |Cite
|
Sign up to set email alerts
|

Patency of Litomosoides sigmodontis infection depends on Toll‐like receptor 4 whereas Toll‐like receptor 2 signalling influences filarial‐specific CD4+ T‐cell responses

Abstract: Summary BALB/c mice develop a patent state [release of microfilariae (Mf), the transmission life‐stage, into the periphery] when exposed to the rodent filariae Litomosoides sigmodontis. Interestingly, only a portion of the infected mice become patent, which reflects the situation in human individuals infected with Wuchereria bancrofti. Since those individuals had differing filarial‐specific profiles, this study compared differences in immune responses between Mf+ and Mf– infected BALB/c mice. We demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…FACS staining was performed as previously described (Rodriogo et al 2016). In brief, cells were fixed and permeabilised with intracellular fixation and permeabilisation buffer set (Thermo Fisher Scientific) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…FACS staining was performed as previously described (Rodriogo et al 2016). In brief, cells were fixed and permeabilised with intracellular fixation and permeabilisation buffer set (Thermo Fisher Scientific) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Primers 1 and 2 were used to detect wildtype allele (1.3 kb), and primers 1 and 3 were used to detect mutant allele (0.5 kb) (Nakae et al 2002 ). The life cycle of L. sigmodontis was maintained in house using infected cotton rats and recovered adult worms were used as the source of L. sigmodontis antigen (LsAg) preparation (Rodriogo et al 2016 ). Protein concentrations of antigenic extracts were determined using the Advanced Protein Assay (Cytoskeleton, ORT, USA) and aliquots of sterile LsAg were frozen at − 80 °C until required.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand mechanisms underlying immunity to filarial infections in man, such as Wuchereria bancrofti which elicits lymphatic filariasis (LF) (2,3), researchers employ the Litomosoides sigmodontis (L. sigmodontis, Ls) rodent model since it reflects several aspects of LF infection. This includes partial patency since only a portion of immunocompetent BALB/c mice become patent (release microfilariae (MF) into the periphery) when naturally infected with Ls (4)(5)(6). The development of adult worms from larval stages in the host provokes different immune reactions and encompasses both innate (neutrophils, eosinophils and basophils) and adaptive responses (T and B cells).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the L. sigmodontis mouse model has been instrumental in understanding the role of Wolbachia beyond the mutualistic relationship with the parasite itself. For example, several studies showed that Toll-like and nucleotide-binding oligomerization domain (NOD)–like receptors and downstream signalling pathways are important for sensing Wolbachia , worm development, MF embryogenesis, and immunity against filariae (Pfarr et al 2003 ; Brattig et al 2004 ; Ajendra et al 2016 ; Rodrigo et al 2016 ; Wiszniewsky et al 2019 ). For a more in-depth review of immune responses to L. sigmodontis in mice, we refer the reader to the recent review by Finlay and Allen ( 2020 ).…”
Section: Human Filarial Speciesmentioning
confidence: 99%